Enhanced strength and ductility in an additively manufactured Al10SiMg alloy at cryogenic temperatures - Muhammad Naeem; Asif Ur Rehman; Liliana Romero Resendiz; Elmas Salamci; Huseyin Aydin; Peyman Ansari; Stefanus Harjo; Wu Gong; Yusuf Usta; Olcay Ersel Canyurt; Xun-Li Wang; Metin U. Salamci (Communications Materials, 2025)
Abstract The increasing demand for lightweight materials that maintain mechanical integrity at ultralow temperatures has driven the development of advanced alloys for cryogenic applications. Additive manufacturing using laser powder bed fusion (LPBF) offers a scalable approach to producing alloys with tailored properties. Here we show that LPBF-manufactured Al10SiMg alloy exhibits significant increase in ultimate tensile strength (395 MPa) and uniform elongation (25%) at an ultralow temperature of 15 K. The enhanced properties result from grain refinement, increased geometrically necessary dislocations, and stress partitioning between the Al matrix and the stiffer Si phase, which supports strain accommodation during deformation. The in-situ neutron diffraction revealed that the Si phase carries most of the load due to its higher yield strength, while the Al matrix experiences continuous strain hardening, enabling an extended deformation capacity. These findings highlight the potential of Al10SiMg for cryogenic applications such as hydrogen storage systems, aerospace components, and quantum computing hardware.